Analysis of the Influence of the MK Consultant's Role on the Performance of Telecommunication Tower Project Implementation - Duden Dodi Hartono (Asian Journal of Social and Humanities, 2023)
Construction Management is an alternative management technique pattern/system in the construction industry development process that combines the stages of the development process into one unit/integration. the effect of implementing a construction management system in the process tower construction Telecommunications can optimize management and control both in terms of cost, time and quality in achieving the goals/targets that have been determined. This writing analyze how far the role, influence of the implementation of the construction management system in the Telecommunication Tower construction process and provide descriptions of the benefits and optimization obtained in its application in terms of cost, quality and time aspects. Project management (planning, organizing, staffing, directing and controlling) has a very large effect on the success of cost performance, quality performance and time performance on the implementation of telecommunications projects with a determination value of 80.3% cost performance affects staffing, directing and planning. Based on the quantitative analysis, the variables that have a major influence on the quality performance used are staffing, directing; and) controlling.